Effects of antimicrobial peptides on growth, morphology of foregut villi and related genes mRNA expression in the common carp (Cyprinus carpio). (16th April 2019) - Dong, Xiao‐Qing; Qu, Gui‐Juan; Chen, Yu‐Ke; Wang, Gui‐Qin; Jiang, Dan
Abstract: A 60‐day feeding trial was conducted to examine the effects of different levels (0, 100, 200, 400 and 600 mg/kg) of antimicrobial peptides on growth, protease activity of foregut, the morphology of foregut villi and related genes mRNA expression level in the common carp ( Cyprinus carpio ). The results showed that the feed of antimicrobial peptides promote common carp growth, and the optimal dosage of antimicrobial peptides is 200–333 mg/kg in the common carp feed. The protease activity of 200 and 400 mg/kg groups were significantly higher than the control and other groups ( p < 0.05). The foregut villus height with 100, 200 and 400 mg/kg antimicrobial peptide groups were significantly higher than control group ( p < 0.05). The crypt depth of 200 and 400 mg/kg antimicrobial peptide groups were significantly lower than control group ( p < 0.05). The ratio of villus height and crypt depth of 100, 200 and 400 mg/kg antimicrobial peptide groups were significantly higher than control group ( p < 0.05). The ratio with 600 mg/kg group was significantly lower than the control group ( p < 0.05). The IGF‐I gene expression level of 200 mg/kg and 400 mg/kg groups were significantly higher than the control group and 600 mg/kg group ( p < 0.05). The IL‐1β gene expression level of 100 mg/kg and 200 mg/kg groups were significantly higher than the control group ( p < 0.05). These results indicated up‐regulation of growth and immune related genes in antimicrobial peptides fed common carp. Correlation analysis showed that IGF‐I mRNA and IL‐1β mRNA were positively correlated with SGR. IL‐1β mRNA and FCR were significantly negative correlated. It indicated that growth and immune gene common regulated the growth of the carp under antimicrobial peptides intervention. In conclusion, antimicrobial peptides can improve growth and related genes mRNA expression in the common carp. Further studies using molecular biological technique or immunologic methods are required to conclude that antimicrobial peptides are beneficial in common carp.